Beyond timber: certification of non-timber forest products - Shanley, P. (2003)
Because the term non-timber forest products encompasses such a vast array of goods, various certification schemes are being applied to them with greater or lesser degrees of success and relevance. This review positions NTFPs within the context of sustainable forest product certification, describing the limitations and adjustments that need to be made for the tool to be applied. Drawing from case studies in Latin America, many impediments to successful implementation of NTFP certification are described including high costs, inaccessibility for small producers, lack of organization among collectors, and lack of adequate land tenure required for certification. In spite of significant obstacles, there are a number of successful experiences that can be expanded to other products. In addition, the process of creating standards has had positive ripple effects among producers, traders, companies and policy makers by planting seeds of a new vision of socially and environmentally responsible forest management.